Effectiveness of the Implementation of the Early Childhood Education – Elementary School Transition Regarding Environmental Introduction for Early Childhood Education Teachers and Elementary School Teachers in Jambi City - Asmorowati, Murni Mei; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to see how effective the implementation of the early childhood education – elementary school transition is regarding the introduction of the school environment for early childhood education teachers and elementary school teachers in Jambi City through the understanding obtained by early childhood education teachers and elementary school teachers about the early childhood education – elementary school transition in Jambi City. The researcher used a quantitative descriptive method by distributing questionnaires to early childhood education teachers and elementary school teachers in Jambi City. With a sample of 75 teachers, the results showed that the level of understanding of early childhood education teachers and elementary school teachers about the early childhood education – elementary school transition in Jambi City regarding the introduction of the school environment was in the "Medium" category of 49.33% (37 teachers), "Low" of 36% (27 teachers), and "High" of 14.67% (11 teachers). Based on the average value, which is 3.28%, the level of understanding of early childhood education teachers and elementary school teachers about the early childhood education – elementary school transition regarding the introduction of the school environment in Jambi City is in the "MEDIUM" category.